2008
DOI: 10.4236/jmmce.2008.72011
|View full text |Cite
|
Sign up to set email alerts
|

Sigma Phase Formation and Embrittlement of Cast Iron-Chromium-Nickel (Fe-Cr-Ni) Alloys

Abstract: HK alloy is a member of the heat resistant cast alloy family (H-Series) steels. They are widely used in the petrochemical industry for components requiring enhanced high temperature properties. Microstructural changes occurring at high temperature clearly affects its mechanical properties. These properties have been shown in HK-40 steel subjected to high-temperature degradation and prone to the formation of sigma phase. The investigation carried out included metallurgical analysis, materials characterization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
(19 reference statements)
3
16
0
1
Order By: Relevance
“…In addition to the small and rounded carbides inside the austenite grains, coarser and plate or needlelike precipitates of sigma phases are observed within the grains. Similar microstructural features showing plate or needlelike precipitates of sigma phases have been observed by Babakr et al [2] and Łabanowski [7].…”
Section: Microstructural Examinationsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition to the small and rounded carbides inside the austenite grains, coarser and plate or needlelike precipitates of sigma phases are observed within the grains. Similar microstructural features showing plate or needlelike precipitates of sigma phases have been observed by Babakr et al [2] and Łabanowski [7].…”
Section: Microstructural Examinationsupporting
confidence: 71%
“…EDS analysis shows the presence of sigma phases along the grain boundary as well as within the grains. Sigma (r) phase is basically an ironchromium intermetallic compound that develops in austenitic stainless steels under prolonged exposure to high temperature (620-900°C) because of thermal instability [2][3][4]. The presence of sigma phase was confirmed by etching the sample with Groesbeck solution [5,6].…”
Section: Microstructural Examinationmentioning
confidence: 99%
“…The role of the coating is pronounced during the transient period of erosion during which it saved the substrate steel from the enhanced E-C loss. The mass loss recorded after the initial transient cycles for both the coatings was meager, which indicates that the coatings could be useful to reduce the It has been reported that sigma (r) phase is hard and fragile, in addition, when forms, it consumes chromium and molybdenum present within the matrix [33], which leads to the depletion in these elements and thereby prevent formation of Cr 2 O 3 . XRD analysis of the exposed coated specimens tested in the given environments indicated that no brittle (sigma) phase was formed in the scales.…”
Section: (A) (B)mentioning
confidence: 97%
“…For the alloys with a Cr content of more than 20%, there is a possibility of forming a σ phase above 550 o C, which also depends on the ageing time and impurity level in the alloy [8]. The formation of the σ phase is detrimental as it makes the material brittle and affects the creep and corrosion properties [9]. The 475 o C embrittlement arises in structural components during service whereas the σ phase embrittlement is produced during heat treatment, welding, or casting.…”
Section: Introductionmentioning
confidence: 99%